How and when supervisors’ information sharing reduces new employees’ errors - Tesfaye A. Bafa; Mingyu Zhang; Chong Chen (South African Journal of Economic and Management Sciences)
Background: Effective supervision through information sharing meaningfully influences employee performance and error reduction. Though the benefits of information sharing are well investigated, its specific impact on new employees’ error reduction in competitive fields, like hotels with various mediators and moderators, is less explored. This research, using the conservation of resources theory, examines how supervisors’ information sharing affects novices’ error reduction, giving attention to the roles of social skills and information seeking.